Carbon leakage, the green paradox and perfect future markets - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2009)
Policies of lowering carbon demand may aggravate rather than alleviate climate change (green paradox). In a two-period three-country general equilibrium model with finite endowment of fossil fuel one country enforces an emissions cap in the first or second period. When that cap is tightened the extent of carbon leakage depends on the interaction of various parameters and elasticities. Conditions for the green paradox are specified. All determinants of carbon leakage resulting from tightening the first-period cap work in opposite direction when the second-period cap is tightened. Tightening the second-period cap does not necessarily lead to the green paradox.
Keywords: H22; Q32; Q54; 330; carbon leakage; green paradox; emissions cap; Klimaschutz; Kohlendioxid; Luftreinhaltung; Immissionsschutz; Wirkungsanalyse; Dynamisches Gleichgewicht; Mehr-Länder-Modell; Theorie